ANALISIS DAN PEMODELAN SPASIAL PERUBAHAN TUTUPAN LAHAN DI HUTAN PRODUKSI TERBATAS KECAMATAN KULAWI KABUPATEN SIGI - Muhammad Adam Suni; Hasriani Muis; Ida Arianingsih; Misra Misra; Rhamdhani Fitrah Baharuddin (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Land conversion is a change in the function of a part or whole land area of its original function (as planned) into another function that becomes a negative impact (problem) on the environment and potential land itself. The study aims to analyze changes in land cover over five years with the image of Landsats 8 of 2016 and 2021 as well as analyze the factors of the cause of changes in land cover in the Limited Production Forest Area in Kulawi Subdistrict. The study used guided image analysis (supervised) and binary logistics regression analysis. The formation of spatial models of forest cover changes in the Kulawi Subdistrict Limited Production Forest Area using 5 modifier factors consisting of accessibility aspects i.e., settlement, population density, river, slope, road. Logit (p)=-0.24087+0.04249(x1)+0.2815(x2)-0.42492(x3)-0,.0480(x4)+0.04010(x5). The results of binary logistic regression analysis showed goodness of fit value of 5471996.86 chi-square values of 60287.17 and pseudo r2 of 0.30 greater than 0.2, indicating the model is worth using. Based on the results of binary logistics regression analysis, it is known that distance from roads, distance from settlement and population density are influential to changes in forest land cover.